"A Win for All of Us": A Counterstory on What Counts as Success in Latinx Students' College Decision-Making - Leslie Patricia Luqueño (MDPI AG, 2024)
This paper utilizes a composite counterstory to address how Latinx first-generation-to-college, low-income students describe what 'success' looks like within their college decision-making processes and counter traditional perspectives on what should matter as they contemplate whether and where to pursue higher education. Building upon calls within college decision-making literature that better encompass the social ecologies of marginalized students, this study centers the voices of 14 Latinx students who apply to college and, oftentimes, challenge educators and mainstream narratives about how they should select which institution to attend. What I found is that students' decision-making processes cannot be explained through mainstream narratives such as meritocracy, undermatching theory, or the importance of school prestige; rather, these discourses, when perpetuated by educators and peers, can be incredibly discouraging and cause dissonance among students. Instead, students portray the importance of family and collective well-being when considering where to pursue college, showing the non-academic prioritizations that shape students' perspectives on 'success'. Overall, this study provides an essential counterstory against deficit perspectives surrounding Latinx first-generation, low-income students' college decision-making and encourages further exploration of how government funding and initiatives can support students regardless of what institution they attend.